2002
DOI: 10.2113/gscanmin.40.5.1375
|View full text |Cite
|
Sign up to set email alerts
|

Systematics in the Structure and Xanes Spectra of Pyroxenes, Amphiboles, and Micas as Derived From Oriented Single Crystals

Abstract: In order to assess the extent of X-ray anisotropy in biaxial minerals, Fe XANES spectra were acquired on single crystals of pyroxenes, amphiboles, and micas with the X-ray beam polarized along the X, Y, and Z optical orientations. Specifically, single crystals of enstatite (En), augite (Aug), aegirine (Ae), kaersutite (Krs; three different compositions), dioctahedral (Ms and Ill), and trioctahedral (Ann and Phl) micas were selected. Each crystal was oriented morphologically and with the aid of EXCALIBR using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
28
0

Year Published

2006
2006
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 28 publications
6
28
0
Order By: Relevance
“…This pre-edge position shifts toward higher energy side with increasing Fe 3+ /ΣFe ratios of minerals by indicating a linear relationship as a function of the Fe 3+ /ΣFe ratio (Bajt et al 1994). A number of research groups employed the XANES techniques and demonstrated its availability for studying the valence state of Fe of terrestrial minerals (Delaney et al 1998;Dyar et al 2001Dyar et al , 2002Wilke et al 2001). In particular, Wilke et al (2001) reported a XANES study of a series of Fe 2+ -and Fe 3+ -bearing minerals with a wide range of coordination environments and concluded that the Fe 3+ contents can be determined with an accuracy of ±10 mol% when the coordination environment is given.…”
Section: Microxanes Analysismentioning
confidence: 97%
See 1 more Smart Citation
“…This pre-edge position shifts toward higher energy side with increasing Fe 3+ /ΣFe ratios of minerals by indicating a linear relationship as a function of the Fe 3+ /ΣFe ratio (Bajt et al 1994). A number of research groups employed the XANES techniques and demonstrated its availability for studying the valence state of Fe of terrestrial minerals (Delaney et al 1998;Dyar et al 2001Dyar et al , 2002Wilke et al 2001). In particular, Wilke et al (2001) reported a XANES study of a series of Fe 2+ -and Fe 3+ -bearing minerals with a wide range of coordination environments and concluded that the Fe 3+ contents can be determined with an accuracy of ±10 mol% when the coordination environment is given.…”
Section: Microxanes Analysismentioning
confidence: 97%
“…The XANES pre-edge position of a single crystalline mineral is known to shift slightly by the effect of X-ray anisotropy (Dyar et al 2002). This anisotropic phenomena appears to produce a limited accuracy in the determination of the Fe 3+ /ΣFe ratio of Chassigny kaersutite, because it is practically difficult to measure an spectra of Chassigny kaersutite with the X-ray beam polarized along the crystalline orientation similar to standard samples.…”
Section: The Pre-edge Peak Position As a Function Of Fe 3+ /σFe Ratiomentioning
confidence: 99%
“…This method has been applied to a wide range of minerals and glasses [35,36,37], although it can potentially be subject to error if the difference in site geometry between the reference standards and the unknowns is too large [35,36]. The centroid positions however do allow systematic trends to be identified and Fig.…”
Section: Fe Oxidation Statementioning
confidence: 99%
“…Delaney et al (1998) reported that the Fe 3+ /∑Fe ratios estimated using XANES analysis are consistent with those Mössbauer estimated using wet chemical analysis. Dyar et al (2001Dyar et al ( , 2002 and Wilke et al (2001) also used Fe XANES spectroscopy to quantitatively estimate the Fe 3+ / ∑Fe ratios for silicate and oxide minerals. Dyar et al (2002) polarized the X-ray beam along the X, Y, and Z optical orientations to obtain Fe XANES spectra from single crystals of pyroxenes, amphiboles, and micas.…”
Section: Introductionmentioning
confidence: 99%
“…Dyar et al (2001Dyar et al ( , 2002 and Wilke et al (2001) also used Fe XANES spectroscopy to quantitatively estimate the Fe 3+ / ∑Fe ratios for silicate and oxide minerals. Dyar et al (2002) polarized the X-ray beam along the X, Y, and Z optical orientations to obtain Fe XANES spectra from single crystals of pyroxenes, amphiboles, and micas. They showed that the pre-edge positions of sheet silicates depend on their crystallographic orientations.…”
Section: Introductionmentioning
confidence: 99%